Four new species of Lorryia (Acari: Tydeidae) associated with Hevea brasiliensis Muell. Arg. (Euphorbiaceae) in Brazil - Mondin, Alexandre De Souza; Nuvoloni, Felipe Micali; Feres, Reinaldo José Fazzio (Zootaxa, 2016)
Lorryia (Tydeinae) species are commonly found in surveys of rubber trees (Hevea brasiliensis) in Brazil, although only Lorryia formosa (Cooreman, 1958) has been formally reported from this host. In this study, we described Lorryia parvireticuli sp. nov., L. amazonensis sp. nov., L. fortistriata sp. nov., and L. virga sp. nov., associated with rubber trees from Brazil.